أثر مستقبل اختلاف الفتوى على تطبيق المنتجات المالية في المصارف الإسلاميّة - Edris, M. (Universiti Sains Islam Malaysia, 2024)
Fatwa is not an easy issue, as Allah (swt) has taken some of its responsibilities Himself e.g. His fatwa about those who leave no descendants or ascendants as heirs. The Prophet Muhammad (saw) has explained the fatwa of Allah (swt) and the scholars after him explained further. As a result of its importance, the Shariah encouraged conveyance of knowledge and warned against concealing it, and vowed to inflict curse of Allah, angles and the people as awhole on persons who are involved in this act. This warning is also extended to those who speak without knowledge. The researcher discusses the difference of fatwa in Islamic banks, noting that there is no difference between the muftis in the principles of Shariah, but the difference stems from the multiplicity of muftis views in some sub-matters. The researcher pointed out that the most prominent differences in fatwa was caused by the long distance between Islamic cities, and this difference arose in thedifferent schools of jurisprudence for multiple factors, and in speculative matters due to differences in peoples minds and perceptions, as the differences was not the main goal, but the goal was to reach to a correct Shariah decision. And the diversity of fatwas by the muftis was a positive thing which is evidence of the capacity and flexibility of the Shariah. And that the recognized fatwa diversity is the one which is based on Shariah proof and other than that is rejected. Indeed, lack of specialized jurists in the contemporary Islamic transactions has caused problem of understanding many new fatwas on how to apply some products. The researcher will highlight all the obstacles, and explain the difference in fatwa. The researcher adopted the critical analytical approach and the deductive approach in order to achieve the desired results. The study consists of two parts: The first part addresses the outlook of fatwa and its future in Islamic banks. And the second part discusses differences of fatwa and its impact on the development and application of Islamic financial products.